A Phase Change Memory Chip Based on TiSbTe Alloy in 40-nm Standard CMOS Technology - Song, Zhitang; Zhan, YiPeng; Cai, Daolin; Liu, Bo; Chen, Yifeng; Ren, Jiadong (Nano-Micro Letters, 2015)
In this letter, a phase change random access memory (PCRAM) chip based on Ti0.4Sb2Te3 alloy material was fabricated in a 40-nm 4-metal level complementary metal-oxide semiconductor (CMOS) technology. The phase change resistor was then integrated after CMOS logic fabrication. The PCRAM was successfully embedded without changing any logic device and process, in which 1.1 V negative-channel metal-oxide semiconductor device was used as the memory cell selector. The currents and the time of SET and RESET operations were found to be 0.2 and 0.5 mA, 100 and 10 ns, respectively. The high speed performance of this chip may highlight the design advantages in many embedded applications.